Facilitators and barriers to employment for persons with chronic spinal cord injury or disorder: A qualitative study framed by the person-environment-occupation model. (4th March 2023) - Dorstyn, Diana S.; Chur-Hansen, Anna; Mansell, Ella; Murphy, Gregory; Roberts, Rachel M.; Stewart, Peter; Potter, Elizabeth; Kneebone, Ian; Craig, Ashley
Abstract : Context/Objective: Prolonged unemployment is common for people living with a spinal cord injury or disorder (SCI/D) and can impact negatively on quality of life. The present study examines stakeholder perspectives and experiences with the job search process in order to identify service gaps and return-to-work solutions. Design: In-depth semi-structured interviews were thematically analysed, with questions focused on factors that can help or hinder efforts to gain employment. Generated themes were then applied to the Person-Environment-Occupation (PEO) systems model of participation. Setting: Community-based disability service provider in South Australia. Participants: Purposive sample of persons with SCI/D ( n  = 8) and rehabilitation professionals ( n  = 4). Results: Person-centred themes were strongly endorsed by both groups and focused on incentives of, and motivation for, employment. Equally important to the job search process were individual expectations and attitudes, particularly job readiness. Environmental facilitators included employers' positive attitude, although workplace discrimination remained a concern. Occupation-based barriers, rather than opportunities, were identified – namely, difficulties in SCI/D self-management, the need for timely functional assessments, and more opportunities for education, upskilling and retraining. Conclusions: The PEO model provides a broad framework to better understand the complex return-to-work process for people with a SCI/D and, potentially, uncover tangible solutions. The suggestion is that vocational rehabilitation should go beyond skills training and include motivational support to enhance job readiness. This must be done on a case-by-case basis. There is also a need for active and covert discrimination to be addressed through employment policies. The findings will be used to develop intervention targets for a newly established vocational rehabilitation service.